Prótesis Transfemoral Electromecánica, Controlada a Base de Señales Mioeléctricas - Andrade Maquilón, Mauricio Ernesto; Paz Ruíz, Nelson Emilio (Universidad Antonio Nariño, 2021)
This paper shows the steps followed for the design and construction of a electromecanically controlled transfemoral prosthesis based on myoelectric signals. The design of the prosthesis was performed in the first place. For this purpose it was necessary to fulfill two processes. The first one consisted of computer-aided design, where the multiple parts and components of the prosthesis were elaborated, according to the desired measurements and dimensions. The second one was a simulation through computer-aided engineering. Here, the prosthesis was computationally tested for motion, strength, speed and position. After carrying out these steps and with the veracity of the adequate functioning of the prosthesis, its construction was performed proposing to give an optimum balance between economy and high standards of product quality. The control of the prosthesis was Sugeno-type fuzzy. It begins with the capture of the non-invasive mode of myoelectric signals by means of surface electrodes under SENIAM recommendations, from the muscle group formed by the biceps femoris, rectus femoris and tensor fascia lata, as well as signals from sensors such as strain gages and accelerometers. This set of signals shows the angle of flexion or extension to which the patient wishes to move the leg. After being treated, these signals are the inputs of a microcontroller which is responsible for its processing and for generating what refers to the control of the actuator component (DC motor), and this is how the prosthesis is moved, according to the level of intention and / or muscle activity of the patient. The purpose of this project has a social emphasis, where this prosthesis is intended to serve as a functional solution to transfemoral amputees and could provide mobility through their myoelectric signals. In addition, developing optimum biomechanical processes and having a balance between economy and quality.